If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -16 + 2 = -2(x + 2) Combine like terms: -16 + 2 = -14 -14 = -2(x + 2) Reorder the terms: -14 = -2(2 + x) -14 = (2 * -2 + x * -2) -14 = (-4 + -2x) Solving -14 = -4 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -14 + 2x = -4 + -2x + 2x Combine like terms: -2x + 2x = 0 -14 + 2x = -4 + 0 -14 + 2x = -4 Add '14' to each side of the equation. -14 + 14 + 2x = -4 + 14 Combine like terms: -14 + 14 = 0 0 + 2x = -4 + 14 2x = -4 + 14 Combine like terms: -4 + 14 = 10 2x = 10 Divide each side by '2'. x = 5 Simplifying x = 5
| 3(2x-7y+1)-3=x-5y+2 | | (7+z)(3z-8)=0 | | -0.6+3.88=-0.8x+0.68 | | 5+2a=3a | | 13a+a^2+40=0 | | -9x-3=60 | | 27-4m=3 | | 6(2x+1)+2=2(4x+1)+2(2x+3) | | 9z-8z=5z+7+3z | | 0=16t^2+8+15 | | 40=(2x-1) | | 10x+5y=95 | | 9C=5F-160 | | -7a-10a= | | 4x+2=7x+7 | | -2x^2+10x-1=0 | | 3=z+6 | | 125w^6+27g^3=0 | | 3x^4-15x^2-72=0 | | 18x^2+15x=0 | | -20+7z+6z^2=0 | | 7x+15= | | 2x^2-7x=-6 | | 6t^2-96=0 | | 18x^2+21x=0 | | 7+2t+3t= | | -6wx^5(3w^6+4w^3x^4-9x^4)= | | 4a+12=3a+32 | | 13-2x=x^2-25 | | x^2+21=5 | | 7-2k=15 | | 6.7+12m-9.3=6.4 |